2012
DOI: 10.1084/jem.20120596
|View full text |Cite
|
Sign up to set email alerts
|

The cell fate determinant Llgl1 influences HSC fitness and prognosis in AML

Abstract: Inactivation of Llgl1 enhances HSC self-renewal and fitness and is associated with unfavorable outcome in human AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 29 publications
(42 reference statements)
5
37
0
Order By: Relevance
“…These experiments were performed similar as described earlier (24,25). Details are provided in the SI.…”
Section: Leukemia Model With Engineered Primary Mouse Hematopoietic Smentioning
confidence: 99%
“…These experiments were performed similar as described earlier (24,25). Details are provided in the SI.…”
Section: Leukemia Model With Engineered Primary Mouse Hematopoietic Smentioning
confidence: 99%
“…The cyclin-dependent kinases (CDK) CDK6 and Src family kinases (SFKs) inhibit expression of EGR1 (81,82). On the contrary, Llgl1 (lethal giant larvae homolog 1) and PMA (Phorbol 12-myristate 13-acetate) contribute to the differentiation of hematopoietic stem cells (83,84). Andra Schaefer et al found that the expression of EGR-1 had a regulatory role in Epo signal transduction in leukemia cells (85).…”
Section: Pathogenesis Mechanism Of Aml By Egr1mentioning
confidence: 99%
“…Llgl1 null mice develop severe brain dysplasia and die at birth from extensive hydrocephalus (Klezovitch et al 2004). In addition, Lgl1 null mice show defects in the development of the retina (Clark et al 2012), and loss of Llgl1 enhances hematopoietic cell numbers and activity (Heidel et al 2013). In contrast to zebrafish, Llgl2 null mice are viable and show no gross phenotypes, albeit Llgl2 appears to be necessary for branching morphogenesis during placental development (Sripathy et al 2011).…”
Section: Mus Musculusmentioning
confidence: 99%
“…Many studies have shown, using knockdown approaches, that Scribble and Dlg play key roles in the response of T and B cells to antigen presentation Round et al 2005Round et al , 2007Humphries et al 2012;Ludford-Menting et al 2005;Xavier et al 2004). However, gene knockout studies have shown minimal and/or transient effects of deletion of Scribble, Lgl1, and Dlg1 on hematopoiesis and immune cell function Hawkins et al 2013Hawkins et al , 2014Humphries et al 2012;Heidel et al 2013). The discrepancy between knockdown and knockout studies is thought to reflect compensatory mechanisms by which lymphocytes might adjust to deletion of the Scribble module genes over time (Humphries et al 2012;Pham et al 2014), and further studies are required to resolve this discrepancy.…”
Section: The Immune Synapsementioning
confidence: 99%